Pelaksanaan Kegiatan Literasi Sekolah untuk Membentuk Pembiasaan Gemar Membaca dalam Situasi Pandemi Covid-19 Pada Siswa SD Negeri 13 Kebondalem Kabupaten Pemalang - Pramita Adiningrum; Ikha Listyarini; Filia Prima Artharina (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
During the pandemic, literacy programs in schools were hampered and had difficulty continuing to be implemented. Under these conditions, teachers' efforts to regenerate students' interest in reading during the pandemic are urgently needed so that they can continue to form a generation that has a strong character in knowledge and broad-mindedness. This type of research is qualitative with a qualitative descriptive observation design. The form of research used is a descriptive data method. The population of this study were students of class IV, V and VI SDN13 Kebondalem Pemalang. The sample taken was 30 students using observation, interview, questionnaire, and documentation techniques. The data of this study were obtained through the results of a questionnaire from 4 indicators of reading pleasure that had been made and interviews. Based on the results of the analysis of the data obtained, the indicator of "reading pleasure" is high, "awareness of the benefits of reading" is high, "reading frequency" is quite low for students, and "the quantity of reading resources for students" is high. It can be concluded that the literacy activities carried out at SDN 13 Kebondalem Pemalang have been running well and the habit of reading is formed.